SALURAN DISTRIBUSI DAN MARJIN PEMASARAN KUBIS TOMAT WORTEL - Aflit Nuryulia Praswati; Tulus Prijanto; Bayu Dian Aji (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2018)
Vegetables are an important commodity, whose prices contribute to the inflation rate in some regions of Indonesia. Inflation and deflation are inseparable from the type of food and vegetable groups because the majority of the population have jobs as vegetable farmers. Selo Boyolali is a vegetable-producing region, but currently can not meet the needs of its own region. Supply of vegetables began to decrease due to pest and vegetable turnover into tobacco. If the delivery of vegetables is hampered there will be a scarcity of vegetables that lead to price increases. The length of the distribution channel has a negative impact, namely the price of commodities set by the middlemen or traders who distribute vegetables from the producers. So sometimes local farmers do not have bargaining power on vegetable pricing. This study aims to analyze the pattern of price formation and vegetable distribution in Boyolali. The analytical framework used in this research is supply chain management framework. The method used in this research is quantitative and qualitative indepth interview.